THE ROLE OF AGRARIAN SECTOR IN INCREASING THE FOOD SECURITY OF RUSSIA - A. M. Galiakhmetova (Russian Journal of Economics and Law, 2012)
The article summarizes some theoretical approaches to the notion "food security" as a constituent of national security. The author summarizes and elaborates directions of increasing the food security of Russia in combination with the market mechanism. Factual and normative production volumes are given, taking into account the issues of providing food independence and security. Middle-term predicting indicators are calculated. Special attention is paid to the state support of agricultural production as a mechanism of food secirity provision.